Preparation method and application of high-compactness copper paste for external electrode of MLCC (multilayer ceramic capacitor) product

By optimizing the raw material ratio and process flow of the copper slurry of the outer electrode of MLCC products, the problem of poor density after sintering is solved, and an external electrode with high density and high reliability is achieved.

CN119446657APending Publication Date: 2025-02-14JIANGSU XINSHENG MICROELECTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411806428.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The copper paste of the outer electrode of the existing MLCC products is difficult to achieve ideal density after sintering, and pores are easily formed, which affects the plating quality and the reliability of the outer electrode.

Method used

The thixotropic properties and sintering density of the copper slurry are optimized through specific stirring conditions and sintering schemes using specific raw material ratios and process flows, including the use of copper powder, glass powder and thixotropic agents of different particle sizes and forms.

Benefits of technology

The high density of the outer electrode of MLCC products is achieved, the porosity is reduced, and the plating quality and reliability of the outer electrode are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446657A_ABST
    Figure CN119446657A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of high-compactness copper paste for an external electrode of an MLCC product, and relates to the technical field of external electrode paste. The preparation method of the high-compactness copper paste specifically comprises the following steps: S1, raw material preparation: weighing the metal copper powder, the binder, the organic solvent, the glass powder and the thixotropic agent; preparing for later use; s2, preparing an organic carrier: adding a binder into an organic solvent, and stirring until the binder is completely dissolved to obtain the organic carrier; s3, mixing the copper powder and the glass powder: mixing the metal copper powder and the glass powder, slowly adding the organic carrier, and stirring until the solution is uniform to obtain a mixture A; s4, thixotropic agent adding and mixing, specifically, the thixotropic agent is slowly added into the mixture A, stirring is conducted, and the high-compactness copper paste is obtained; the application process comprises the steps that the high-compactness copper paste is dip-plated to the designated surface position of an MLCC product, sintering is conducted for 1-1.5 h at the temperature of 550-850 DEG C, and an outer electrode is obtained. The external electrode prepared in this way has high compactness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of external electrode slurry, and specifically to a preparation method and application of high-density copper slurry for external electrodes of MLCC products. Background Art

[0002] MLCC (Multilayer Ceramic Capacitor): A capacitor made of multiple layers of ceramic dielectrics and electrodes alternately stacked, with the advantages of small size and large capacity, is widely used in circuits in electronic devices for functions such as storing and releasing electrical energy. As an indispensable key electronic component in modern electronic devices, MLCC is widely used in circuits of various electronic products, and it undertakes important functions such as storing and releasing electrical energy. As the key part of the connection between MLCC and the external circuit, the quality of the external electrode is directly related to the overall performance of MLCC. At present, the preparation of the external electrode is generally achieved by copper paste through immersion plating, sintering and other processes. However, in actual production practice, a prominent problem has gradually emerged, that is, after the existing external electrode copper paste completes the sintering process, the formed external electrode is often difficult to achieve the ideal density state, and pores are easily formed. In the subsequent electroplating process, the pore structure of the external electrode becomes a "convenient channel" for the invasion of electroplating solution. Once the chemical penetrates, on the one hand, it will react chemically with the copper electrode, causing corrosion to it, and significantly reducing the conductivity of the electrode; on the other hand, the invasion of the chemical may also destroy the relatively weak adhesion between the copper paste and the MLCC ceramic substrate, causing the external electrode to loosen or even fall off, which undoubtedly has an extremely adverse effect on the performance and reliability of MLCC products, and has become one of the important bottlenecks restricting the further improvement of MLCC product performance.

[0003] In the existing relevant technical fields, most of the formulations and application solutions for MLCC external electrode copper paste are mainly based on some conventional ideas and practices. For example, in terms of the basic composition of copper paste, metal copper powder with a certain purity and particle size range is usually selected as the main conductive component. The common copper powder purity is about 99%, and the particle size distribution is mostly in the range of 2 to 8 μm. At the same time, an organic carrier composed of a binder, an organic solvent, etc. is used to achieve the bonding of copper powder and the adjustment of the viscosity of the copper paste to ensure that it has suitable fluidity for immersion plating operations. In addition, an appropriate amount of glass powder is added, the main function of which is to play a fluxing function during the sintering process, and to improve the adhesion between the copper paste and the MLCC ceramic matrix to a certain extent. In terms of the preparation process, the above components are often simply mixed and stirred in a certain proportion to form a usable copper paste, and then the conventional operation steps such as immersion plating and sintering are directly carried out. In actual applications, a series of technical defects have been exposed. First, in the copper paste formula design process, although the selection and ratio of each component can meet the basic functional requirements such as conductivity and bonding, it has not fully considered how to fundamentally improve the density of the external electrode after sintering. For example, the particle size range of the selected copper powder is relatively wide, which makes it difficult for the copper powder particles to be arranged tightly and orderly during the sintering process, resulting in the formation of external electrodes with more pores and poor density. Secondly, in terms of preparation technology, it is only a simple mixing and stirring operation, which cannot finely control the microstructure and properties of the copper paste, and cannot give full play to the synergistic effect between the components to improve the sintering density.

[0004] In summary, in order to solve the above problems, it is of great significance to provide a preparation method and a use method of a high-density copper paste for the external electrode of MLCC products. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method and application of high-density copper paste for external electrodes of MLCC products to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The method for preparing high-density copper paste for the external electrode of MLCC products comprises the following steps:

[0008] S1: Raw material preparation: weigh metal copper powder, binder, organic solvent, glass powder and thixotropic agent and set aside;

[0009] S2: Organic carrier preparation: adding the binder into the organic solvent and stirring until it is completely dissolved to obtain the organic carrier;

[0010] S3: Mixing copper powder and glass powder: After mixing the metal copper powder and the glass powder, slowly add the organic carrier and stir until the solution is uniform to obtain a mixture A;

[0011] S4: Adding and mixing thixotropic agent: slowly add the thixotropic agent into mixture A and stir to obtain a high-density copper slurry.

[0012] Preferably, the raw materials of the high-density copper paste include the following substances, calculated by mass: 75-80 parts of metal copper powder, 10-12 parts of binder, 35-40 parts of organic solvent, 4-5 parts of glass powder, and 2.5-3 parts of thixotropic agent.

[0013] Wherein, the organic solvent includes terpineol; the thixotropic agent includes fumed silica with a specific surface area of ​​220 to 250 m 2 / g; the binder includes an acrylic polymer with a molecular weight of 150,000 to 200,000; and the glass powder D50 is 1 to 2 μm.

[0014] Preferably, in step S2, during the stirring process, the temperature is 50-70°C and the stirring speed is 500-1000 r / min; in step S3, during the stirring process, the stirring speed is 1000-2000 r / min; in step S4, during the stirring process, the stirring speed is 500-1000 r / min and the time is 30-60 min.

[0015] The metal copper powder includes the following substances, calculated by mass: 40-45 parts of flaky copper powder with a D50 of 2-4 μm, 35-40 parts of quasi-spherical copper powder with a D50 of 1-2 μm, and 20-25 parts of spherical copper powder with a D50 of 0.5-1 μm.

[0016] Preferably, during the mixing process of the copper powder and the glass powder, the spherical copper powder with a D50 of 1 to 2 μm and the glass powder are first mixed evenly, and then the remaining copper powder is added and mixed.

[0017] Preferably, in the binder, the mass ratio of acrylic polymer to branched polymer is 1:0.8 to 1.2.

[0018] Preferably, the preparation method of the branched polymerization comprises the following steps:

[0019] (1) adding cis-2,3-divinylethylene oxide to an aqueous solution containing 4-6 wt% of sodium tetrapropylenebenzenesulfonate, stirring evenly, adding tris(hydroxymethyl)aminomethane, stirring for 2-4 hours at 80-90° C. under nitrogen flow, breaking the emulsion, and purifying to obtain a branched monomer A;

[0020] (2) Add methyl methacrylate and branched monomer A to ethyl acetate and stir for 15 to 20 minutes, add dodecanethiol and azobisisobutyronitrile, stir at 80 to 85° C. for 3 to 4 hours, then stand at 85 to 95° C. for 30 to 40 minutes, cool to room temperature, filter, wash, and dry to obtain a branched polymer.

[0021] The branched monomer A comprises the following raw materials in parts by weight: 6 to 7 parts of cis-2,3-divinylethylene oxide, 40 to 50 parts of sodium tetrapropylenebenzenesulfonate aqueous solution, and 9 to 11 parts of trishydroxymethylaminomethane; the branched polymer comprises the following raw materials in parts by weight: 24 to 26 parts of methyl methacrylate, 5 to 6 parts of branched monomer A, 50 to 60 parts of ethyl acetate, 5 to 6 parts of dodecanethiol, and 0.2 to 0.3 parts of azobisisobutyronitrile.

[0022] Preferably, the application process of the high-density copper paste for the external electrode of the MLCC product is: immersion-plating the high-density copper paste to the specified surface position of the MLCC product, sintering at 550-850°C for 1-1.5h to obtain the external electrode.

[0023] Preferably, during the sintering process, the temperature is first kept at 550-650° C. for 20-30 min, then the temperature is increased to 700-850° C. at a rate of 4.5-6.5° C. / min, and then sintered for 10-15 min.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The components of the present invention are added in a specific order and stirred under specific conditions (temperature, rotation speed, time) to achieve precise control of the thixotropic properties of the copper slurry and the final sintering density. The present invention uses fumed silica as a thixotropic agent. In the preparation process of the copper slurry, it is slowly added to the system in the last step. The thixotropic agent will be fully dispersed and interact with other components. The timing of adding the thixotropic agent and stirring conditions play an extremely critical role in optimizing the thixotropic properties of the copper slurry and the final density after sintering.

[0026] (2) The present invention adopts copper powders of different particle sizes and different forms to be mixed and added. The copper powder forms are generally divided into spherical copper powder, quasi-spherical copper powder, flake copper powder, etc. Compared with spherical copper powder, flake copper powder has a larger contact area between copper powders and is more compact after sintering. However, when used alone for sintering, the arrangement of copper powders between copper powders is prone to unevenness due to their flake structures, resulting in local voids and high costs. Therefore, the present invention adopts quasi-spherical copper powder with a particle size of 1 to 2 μm, spherical copper powder with a particle size of 0.5 to 1 μm, and flake copper powder with a particle size of 2 to 4 μm. Copper powder with a smaller particle size can assist in filling the voids and improve the density. At the same time, since copper powder with a small particle size will start to approach the molten state earlier during the sintering process, it plays a bridging role and promotes the density after sintering. The added glass powder can help the sintering. When the temperature reaches the glass softening temperature, the softened glass will gradually fill the remaining gaps in the copper powder, wet the copper powder, and form a film with the copper powder. Under the action of microscopic forces such as surface forces, the copper powder will be rearranged and become regular and compact. The contact points will form sintering necks and gradually expand, and the gaps will gradually decrease to reach a microporous state. At the same time, the glass liquid will fill the micropores, thereby improving the density after sintering. At the same time, the present invention also limits the particle size of the glass powder to 1-2 μm, and pre-mixes the spherical copper powder of 1-2 μm with the glass powder, and then adds the remaining copper powder, which helps to reduce the agglomeration of the glass powder, improve the dispersibility, and thus improve the density after sintering.

[0027] (3) The present invention replaces a portion of the binder acrylic polymer with a branched polymer without changing the thixotropy of the copper paste, so as to improve the dispersibility of the copper paste; thereby improving the sintering performance and increasing the uniform density after sintering.

[0028] The branched polymer is prepared by polymerization using methyl methacrylate as a main monomer, polyhydroxy-modified cis-2,3-divinyl oxirane as a branching monomer, azobisisobutyronitrile as an initiator, and dodecanethiol as a chain transfer agent; the main chain segment is methyl methacrylate, which can provide basic viscosity, and the branched chain segment is a modified polyhydroxy chain segment, which helps to form intermolecular hydrogen bonds, plays an anti-sedimentation role, and improves the dispersion uniformity of copper powder and glass powder; the branched polymer has a three-dimensional spherical structure, the viscosity is not particularly large, the flowability is good, and the particles can be prevented from being unevenly dispersed due to high viscosity; the branched polymer has good wettability to glass and ceramics, and has high density after sintering.

[0029] (4) In the process of sintering the copper paste of the present invention, the optimized sintering scheme is: firstly heat up to 550-650°C and maintain for a period of time, and then continue to heat up to 700-850°C at a specific heating rate; during the process, 550-650°C is at the critical temperature for softening the glass powder, so that the copper powder is preliminarily arranged, which is conducive to uniform sintering and better infiltration, and can also prevent excessive temperature from causing excessive liquid glass in the local area, causing it to overflow from the surface of the copper film, resulting in loose connection between the subsequent coating and the alloy, and reduced density. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 : Flow chart of copper paste preparation process;

[0031] Figure 2 : Diagram of the external electrode structure after copper paste sintering. DETAILED DESCRIPTION

[0032] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.

[0033] It should be noted that there is no special restriction on the purchase manufacturers of all raw materials involved in the present invention, which exemplarily include: copper powder, purity 99.8%, particle size D50 of 1 to 4 μm; glass powder (Al-Si-BKO), purity 99%, particle size D50 of 1 to 2 μm, and softening point of 550°C; acrylic polymer, purity 99%, provided by Nanjing Bermuda Biotechnology Co., Ltd.; flaky copper powder: purity 99.9%, particle size D50 of 2 to 4 μm; quasi-spherical copper powder: purity 99.9%, particle size D50 of 1 to 2 μm; spherical copper powder: purity 99.9%, particle size D50 of 0.5 to 1 μm; cis-2,3-divinyl oxirane: cas:13051-60-0; trishydroxymethylaminomethane: cas:77-86-1; methyl methacrylate, purity 99%, provided by Mingwei (Shandong) Supply Chain Management Co., Ltd.

[0034] In the following examples, parts are by mass and all raw materials are commercially available.

[0035] Embodiment 1:

[0036] Step 1: Preparation of copper paste:

[0037] S1: Raw material preparation: accurately weigh 80 parts of metal copper powder with a particle size D50 of 2 to 4 μm, 10 parts of acrylic polymer with a molecular weight of 200,000, 40 parts of pine alcohol, 5 parts of glass powder and 3 parts of a specific surface area of ​​250 m 2 / g of thixotropic agent; spare;

[0038] S2: Organic carrier preparation: adding the binder into the organic solvent and stirring at 60°C until it is completely dissolved to obtain an organic carrier;

[0039] S3: Mixing copper powder and glass powder: After mixing the metal copper powder and the glass powder, slowly add the organic carrier, and stir at a speed of 1500 r / min until the solution is uniform to obtain a mixture A;

[0040] S4: Adding and mixing thixotropic agent: slowly add the thixotropic agent into mixture A, and stir at a speed of 750 r / min for 45 min to obtain a high-density copper slurry.

[0041] Step 2: Sintering of copper paste:

[0042] The copper paste is dip-plated onto the designated surface position of the MLCC product through an immersion plating device, transferred to a sintering device, and sintered at 800°C in a nitrogen atmosphere for 1 hour to obtain an external electrode.

[0043] Embodiment 2:

[0044] Step 1: Preparation of copper paste:

[0045] S1: Raw material preparation: Accurately weigh 75 parts of copper powder with a D50 of 1-3 μm, 12 parts of acrylic polymer with a molecular weight of 150,000, 35 parts of pinene alcohol, 4 parts of glass powder and 2.5 parts of a specific surface area of ​​220 m 2 / g of thixotropic agent; spare;

[0046] S2: Organic carrier preparation: adding the binder into the organic solvent and stirring at 60°C until it is completely dissolved to obtain an organic carrier;

[0047] S3: Mixing copper powder and glass powder: After mixing the metal copper powder and the glass powder, slowly add the organic carrier, and stir at a speed of 1500 r / min until the solution is uniform to obtain a mixture A;

[0048] S4: Adding and mixing thixotropic agent: slowly add the thixotropic agent into mixture A, and stir at a speed of 750 r / min for 45 min to obtain a high-density copper slurry.

[0049] Step 2: Sintering of copper paste:

[0050] The copper paste is dip-plated onto the designated surface position of the MLCC product through an immersion plating device, transferred to a sintering device, and sintered at 750°C in a nitrogen atmosphere for 1 hour to obtain an external electrode.

[0051] Embodiment 3:

[0052] The metal copper powder includes the following raw materials by weight: 40-45 parts of flake copper powder with a D50 of 2-4 μm, 35-40 parts of quasi-spherical copper powder with a D50 of 1-2 μm, and 20-25 parts of spherical copper powder with a D50 of 0.5-1 μm.

[0053] Step 1: Preparation of copper paste:

[0054] S1: Raw material preparation: Accurately weigh 75 parts of metal copper powder, 12 parts of acrylic polymer with a molecular weight of 150,000, 35 parts of pine alcohol, 4 parts of glass powder and 2.5 parts of a specific surface area of ​​220 m 2 / g of thixotropic agent; spare;

[0055] S2: Organic carrier preparation: adding the binder into the organic solvent and stirring at 60°C until it is completely dissolved to obtain an organic carrier;

[0056] S3: Mixing copper powder and glass powder: After mixing the metal copper powder and the glass powder, slowly add the organic carrier, and stir at a speed of 1500 r / min until the solution is uniform to obtain a mixture A;

[0057] S4: Adding and mixing thixotropic agent: slowly add the thixotropic agent into mixture A, and stir at a speed of 750 r / min for 45 min to obtain a high-density copper slurry.

[0058] Step 2: Sintering of copper paste:

[0059] The copper slurry is dip-plated onto the designated surface position of the MLCC product through an immersion plating device, and then transferred to a sintering device. It is first kept at 600°C in a nitrogen atmosphere for 25 minutes, then heated to 750°C at a rate of 5°C / min, and then sintered for 10 minutes to obtain an external electrode.

[0060] Embodiment 4:

[0061] The metal copper powder includes the following raw materials by weight: 40-45 parts of flake copper powder with a D50 of 2-4 μm, 35-40 parts of quasi-spherical copper powder with a D50 of 1-2 μm, and 20-25 parts of spherical copper powder with a D50 of 0.5-1 μm.

[0062] Step 1: Preparation of branched polymer:

[0063] (1) adding 6.5 parts of cis-2,3-divinyl oxirane to 45 parts of an aqueous solution containing 5 wt% of sodium tetrapropylene benzene sulfonate, stirring evenly, adding 10 parts of tris(hydroxymethyl)aminomethane, stirring at 85° C. under nitrogen flow for 3 h, breaking the emulsion, and purifying to obtain branched monomer A;

[0064] (2) Add 25 parts of methyl methacrylate and 5.5 parts of branched monomer A to 55 parts of ethyl acetate and stir for 15 minutes, add 5.5 parts of dodecanethiol and 0.25 parts of azobisisobutyronitrile, stir at 85°C for 3.5 hours, then stand at 90°C for 35 minutes, cool to room temperature, filter, wash, and dry to obtain a branched polymer.

[0065] Step 2: Preparation of copper paste:

[0066] S1: Raw material preparation: Accurately weigh 75 parts of metal copper powder, 6 parts of acrylic polymer with a molecular weight of 150,000, 6 parts of branched polymer, 35 parts of pinene alcohol, 4 parts of glass powder and 2.5 parts of a specific surface area of ​​220 m 2 / g of thixotropic agent; spare;

[0067] S2: Organic carrier preparation: adding the binder into the organic solvent and stirring at 60°C until it is completely dissolved to obtain an organic carrier;

[0068] S3: Mixing copper powder and glass powder: After mixing the metal copper powder and the glass powder, slowly add the organic carrier, and stir at a speed of 1500 r / min until the solution is uniform to obtain a mixture A;

[0069] S4: Adding and mixing thixotropic agent: slowly add the thixotropic agent into mixture A, and stir at a speed of 750 r / min for 45 min to obtain a high-density copper slurry.

[0070] Step 3: Sintering of copper paste:

[0071] The copper slurry is dip-plated onto the designated surface position of the MLCC product through an immersion plating device, and then transferred to a sintering device. It is first kept at 600°C in a nitrogen atmosphere for 25 minutes, then heated to 750°C at a rate of 5°C / min, and then sintered for 10 minutes to obtain an external electrode.

[0072] Comparative Example 1: Based on Example 2, the raw materials were directly mixed, and the rest of the process remained unchanged:

[0073] Step 1: Preparation of copper paste:

[0074] S1: Raw material preparation: Accurately weigh 75 parts of copper powder with a D50 of 1-3 μm, 12 parts of acrylic polymer with a molecular weight of 150,000, 35 parts of pinene alcohol, 4 parts of glass powder and 2.5 parts of a specific surface area of ​​220 m 2 / g of thixotropic agent; spare;

[0075] S2: Mix the raw materials, stir at 60° C. and 1000 r / min for 1 h to obtain a high-density copper slurry.

[0076] Step 2: Sintering of copper paste:

[0077] The copper paste is dip-plated onto the designated surface position of the MLCC product through an immersion plating device, transferred to a sintering device, and sintered at 750°C in a nitrogen atmosphere for 1 hour to obtain an external electrode.

[0078] Comparative Example 2: Based on Example 4, all spherical copper powders were used, and the other processes remained unchanged:

[0079] The metal copper powder includes spherical copper powder with a D50 of 2 to 4 μm;

[0080] Step 1: Preparation of branched polymer:

[0081] (1) adding 6.5 parts of cis-2,3-divinyl oxirane to 45 parts of an aqueous solution containing 5 wt% of sodium tetrapropylene benzene sulfonate, stirring evenly, adding 10 parts of tris(hydroxymethyl)aminomethane, stirring at 85° C. under nitrogen flow for 3 h, breaking the emulsion, and purifying to obtain branched monomer A;

[0082] (2) Add 25 parts of methyl methacrylate and 5.5 parts of branched monomer A to 55 parts of ethyl acetate and stir for 15 minutes, add 5.5 parts of dodecanethiol and 0.25 parts of azobisisobutyronitrile, stir at 85°C for 3.5 hours, then stand at 90°C for 35 minutes, cool to room temperature, filter, wash, and dry to obtain a branched polymer.

[0083] Step 2: Preparation of copper paste:

[0084] S1: Raw material preparation: Accurately weigh 75 parts of metal copper powder, 6 parts of acrylic polymer with a molecular weight of 150,000, 6 parts of branched polymer, 35 parts of pinene alcohol, 4 parts of glass powder and 2.5 parts of a specific surface area of ​​220 m 2 / g of thixotropic agent; spare;

[0085] S2: Organic carrier preparation: adding the binder into the organic solvent and stirring at 60°C until it is completely dissolved to obtain an organic carrier;

[0086] S3: Mixing copper powder and glass powder: After mixing the metal copper powder and the glass powder, slowly add the organic carrier, and stir at a speed of 1500 r / min until the solution is uniform to obtain a mixture A;

[0087] S4: Adding and mixing thixotropic agent: slowly add the thixotropic agent into mixture A, and stir at a speed of 750 r / min for 45 min to obtain a high-density copper slurry.

[0088] Step 3: Sintering of copper paste:

[0089] The copper slurry is dip-plated onto the designated surface position of the MLCC product through an immersion plating device, and then transferred to a sintering device. It is first kept at 600°C in a nitrogen atmosphere for 25 minutes, then heated to 750°C at a rate of 5°C / min, and then sintered for 10 minutes to obtain an external electrode.

[0090] Comparative Example 3: Based on Example 4, the sintering temperature was directly increased to 750°C, and the other processes remained unchanged:

[0091] The metal copper powder includes the following raw materials by weight: 40-45 parts of flake copper powder with a D50 of 2-4 μm, 35-40 parts of quasi-spherical copper powder with a D50 of 1-2 μm, and 20-25 parts of spherical copper powder with a D50 of 0.5-1 μm.

[0092] Step 1: Preparation of branched polymer:

[0093] (1) adding 6.5 parts of cis-2,3-divinyl oxirane to 45 parts of an aqueous solution containing 5 wt% of sodium tetrapropylene benzene sulfonate, stirring evenly, adding 10 parts of tris(hydroxymethyl)aminomethane, stirring at 85° C. under nitrogen flow for 3 h, breaking the emulsion, and purifying to obtain branched monomer A;

[0094] (2) Add 25 parts of methyl methacrylate and 5.5 parts of branched monomer A to 55 parts of ethyl acetate and stir for 15 minutes, add 5.5 parts of dodecanethiol and 0.25 parts of azobisisobutyronitrile, stir at 85°C for 3.5 hours, then stand at 90°C for 35 minutes, cool to room temperature, filter, wash, and dry to obtain a branched polymer.

[0095] Step 2: Preparation of copper paste:

[0096] S1: Raw material preparation: Accurately weigh 75 parts of metal copper powder, 6 parts of acrylic polymer with a molecular weight of 150,000, 6 parts of branched polymer, 35 parts of pinene alcohol, 4 parts of glass powder and 2.5 parts of a specific surface area of ​​220 m 2 / g of thixotropic agent; spare;

[0097] S2: Organic carrier preparation: adding the binder into the organic solvent and stirring at 60°C until it is completely dissolved to obtain an organic carrier;

[0098] S3: Mixing copper powder and glass powder: After mixing the metal copper powder and the glass powder, slowly add the organic carrier, and stir at a speed of 1500 r / min until the solution is uniform to obtain a mixture A;

[0099] S4: Adding and mixing thixotropic agent: slowly add the thixotropic agent into mixture A, and stir at a speed of 750 r / min for 45 min to obtain a high-density copper slurry.

[0100] Step 3: Sintering of copper paste:

[0101] The copper paste is dip-plated onto the designated surface position of the MLCC product through an immersion plating device, transferred to a sintering device, and sintered at 750°C in a nitrogen atmosphere for 1 hour to obtain an external electrode.

[0102] Comparative Example 4: Based on Example 4, linear polymethyl methacrylate was used instead, and the rest of the process remained unchanged:

[0103] The metal copper powder includes the following raw materials by weight: 40-45 parts of flake copper powder with a D50 of 2-4 μm, 35-40 parts of quasi-spherical copper powder with a D50 of 1-2 μm, and 20-25 parts of spherical copper powder with a D50 of 0.5-1 μm.

[0104] Step 1: Preparation of copper paste:

[0105] S1: Raw material preparation: Accurately weigh 75 parts of metallic copper powder, 6 parts of acrylic polymer with a molecular weight of 150,000, 6 parts of linear polymethyl methacrylate, 35 parts of pine alcohol, 4 parts of glass powder and 2.5 parts of a specific surface area of ​​220 m 2 / g of thixotropic agent; spare;

[0106] S2: Organic carrier preparation: adding the binder into the organic solvent and stirring at 60°C until it is completely dissolved to obtain an organic carrier;

[0107] S3: Mixing copper powder and glass powder: After mixing the metal copper powder and the glass powder, slowly add the organic carrier, and stir at a speed of 1500 r / min until the solution is uniform to obtain a mixture A;

[0108] S4: Adding and mixing thixotropic agent: slowly add the thixotropic agent into mixture A, and stir at a speed of 750 r / min for 45 min to obtain a high-density copper slurry.

[0109] Step 2: Sintering of copper paste:

[0110] The copper slurry is dip-plated onto the designated surface position of the MLCC product through an immersion plating device, and then transferred to a sintering device. It is first kept at 600°C in a nitrogen atmosphere for 25 minutes, then heated to 750°C at a rate of 5°C / min, and then sintered for 10 minutes to obtain an external electrode.

[0111] Performance test: (1) Thixotropic performance test: The copper paste samples prepared in each embodiment were defoamed and added to the measurement system of Anton Paar's MCR series rheometer. The dynamic oscillation mode was used: the measurement frequency range was set to 0.1-10 Hz, and the strain amplitude was set to 0.1-1%. The thixotropic properties of the copper paste were evaluated by observing the viscosity of the copper paste in a static state (i.e., the shear rate was 0 s-1) and the decrease and recovery of the viscosity after the shear rate was applied. The thixotropic properties of the copper paste were evaluated as excellent, good, medium, and poor (excellent: able to flow rapidly when subjected to external force and quickly restore the original structure after the external force was removed; good: able to flow moderately when subjected to external force and quickly restore to the initial state after the external force stopped; medium: the flow performance was acceptable when subjected to external force, but the speed of restoring the initial state was slow; poor: the flow performance was poor when subjected to external force, and it was difficult to restore to the initial state after the external force was removed). The experimental data are shown in Table 1. (2) Density test: The samples were scanned and observed using a scanning electron microscope, and Avizo The 3D software was used to analyze the electrode surface images, obtain the void area and non-void area, and calculate the porosity. The experimental data are shown in Table II .

[0112] Table 1

[0113] project Thixotropic properties Example 1 good Example 2 good Example 3 good Example 4 excellent Comparative Example 4 middle

[0114] Table 2

[0115]

[0116]

[0117] Conclusion: It can be seen from the table that, compared with Example 2, Examples 4 and 3 gradually increase the mixing of copper powders of different specifications and the introduction of branched polymers in the adhesive, and the thixotropic properties of the solution are slightly increased, while the porosity gradually decreases; Comparative Example 4 replaces the branched polymer in the adhesive with linear polymethyl methacrylate, and it can be obviously found that the slurry viscosity increases, it is not easy to stir, the thixotropic properties are poor, the raw materials cannot be evenly dispersed, and the porosity is high; Comparative Example 1 is based on Example 2, and the raw materials are directly mixed and added, the slurry system is uneven, resulting in material agglomeration and poor density after sintering; Comparative Example 2, during the sintering process, the contact area between the spherical copper powders is small, the gaps are large after sintering, and the porosity is high; Comparative Example 3, part of the glass liquid overflows the surface, resulting in a decrease in compactness after sintering.

[0118] In summary, the present invention successfully provides a preparation method and application of high-density copper paste for external electrodes of MLCC products through specific raw material ratios, addition order, and mixing conditions. The prepared copper paste has high thixotropy and high density after sintering.

[0119] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing high-density copper paste for external electrodes of MLCC products, characterized in that: The following steps are involved: S1: Raw material preparation: weigh metal copper powder, binder, organic solvent, glass powder and thixotropic agent and set aside; S2: Organic carrier preparation: adding the binder into the organic solvent and stirring until it is completely dissolved to obtain the organic carrier; S3: Mixing copper powder and glass powder: After mixing the metal copper powder and the glass powder, slowly add the organic carrier and stir until the solution is uniform to obtain a mixture A; S4: Adding and mixing thixotropic agent: slowly add the thixotropic agent into mixture A and stir to obtain a high-density copper slurry.

2. The method for preparing a high-density copper paste for external electrodes of MLCC products according to claim 1, characterized in that: The raw materials of the high-density copper paste include the following substances, calculated by mass: 75-80 parts of metal copper powder, 10-12 parts of binder, 35-40 parts of organic solvent, 4-5 parts of glass powder, and 2.5-3 parts of thixotropic agent.

3. The method for preparing a high-density copper paste for external electrodes of MLCC products according to claim 1, characterized in that: The organic solvent includes terpineol; the thixotropic agent includes fumed silica with a specific surface area of ​​220 to 250 m 2 / g; the binder includes an acrylic polymer with a molecular weight of 150,000 to 200,000.

4. The method for preparing a high-density copper paste for an external electrode of an MLCC product according to claim 1, characterized in that: In step S2, during the stirring process, the temperature is 50-70°C and the stirring speed is 500-1000r / min; in step S3, during the stirring process, the stirring speed is 1000-2000r / min; in step S4, during the stirring process, the stirring speed is 500-1000r / min and the time is 30-60min.

5. The method for preparing a high-density copper paste for external electrodes of MLCC products according to claim 1, characterized in that: The metal copper powder comprises the following substances, calculated by mass: 40-45 parts of flaky copper powder with D50 of 2-4 μm, 35-40 parts of quasi-spherical copper powder with D50 of 1-2 μm, and 20-25 parts of spherical copper powder with D50 of 0.5-1 μm.

6. The method for preparing high-density copper paste for external electrodes of MLCC products according to claim 3, characterized in that: The binder comprises an acrylic acid polymer and a branched polymer in a mass ratio of 1:0.8-1.

2.

7. The method for preparing a high-density copper paste for external electrodes of MLCC products according to claim 6, characterized in that: The preparation method of the branched polymerization comprises the following steps: (1) adding cis-2,3-divinylethylene oxide to an aqueous solution containing 4-6 wt% of sodium tetrapropylenebenzenesulfonate, stirring evenly, adding tris(hydroxymethyl)aminomethane, stirring for 2-4 hours at 80-90° C. under nitrogen flow, breaking the emulsion, and purifying to obtain a branched monomer A; (2) Add methyl methacrylate and branched monomer A to ethyl acetate and stir for 15 to 20 minutes, add dodecanethiol and azobisisobutyronitrile, stir at 80 to 85° C. for 3 to 4 hours, then stand at 85 to 95° C. for 30 to 40 minutes, cool to room temperature, filter, wash, and dry to obtain a branched polymer.

8. The method for preparing high-density copper paste for external electrodes of MLCC products according to claim 7, characterized in that: The branched monomer A comprises the following raw materials in parts by weight: 6 to 7 parts of cis-2,3-divinylethylene oxide, 40 to 50 parts of sodium tetrapropylenebenzenesulfonate aqueous solution, and 9 to 11 parts of trishydroxymethylaminomethane; the branched polymer comprises the following raw materials in parts by weight: 24 to 26 parts of methyl methacrylate, 5 to 6 parts of branched monomer A, 50 to 60 parts of ethyl acetate, 5 to 6 parts of dodecanethiol, and 0.2 to 0.3 parts of azobisisobutyronitrile.

9. Application of high-density copper paste for external electrodes of MLCC products, characterized by: The high-density copper paste prepared by the preparation method described in any one of claims 1 to 8 is applied to the surface of MLCC products to form external electrodes.

10. The use of high-density copper paste for external electrodes of MLCC products according to claim 9, characterized in that: The application process is: immersion-plating a high-density copper paste onto a designated surface position of the MLCC product, sintering at 550 to 850° C. for 1 to 1.5 hours, and obtaining an external electrode.